2002
DOI: 10.1046/j.1525-1594.2002.06972.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of St. Jude Medical Valve in Patients with Aortic Stenosis and Small Aortic Annulus on Cardiac Function and Late Survival Result

Abstract: This clinical study analyzes our experience of postoperative cardiac function and long-term survival rate in patients with aortic stenosis and small-size St. Jude Medical (SJM) valve. Sixty-eight patients who underwent aortic valve replacement by SJM valve were divided into two groups by preoperative aortic annulus diameter. Group 1 consisted of 44 patients with small aortic annulus and small-size SJM valve (19 mm or 21 mm). In Group 1, small SJM standard valves were implanted in 16 patients, and small SJM Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently, different authors have reported excellent clinical and hemodynamic outcomes in patients undergoing AVR with a SJMR mechanical aortic prosthesis . The SJMR has a significantly better hemodynamic performance in terms of postoperative EOA and transprosthetic gradients versus SJMHP for the respective valve sizes . In the present study we report two series of patients undergoing SJMR‐17 and SJMHP‐17, respectively.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Recently, different authors have reported excellent clinical and hemodynamic outcomes in patients undergoing AVR with a SJMR mechanical aortic prosthesis . The SJMR has a significantly better hemodynamic performance in terms of postoperative EOA and transprosthetic gradients versus SJMHP for the respective valve sizes . In the present study we report two series of patients undergoing SJMR‐17 and SJMHP‐17, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Niinami et al demonstrated similar hemodynamic performance in terms of transprosthetic gradients in patients undergoing AVR with SJMHP‐19 compared to SJMSD‐19. Other studies demonstrated acceptable clinical and hemodynamic outcomes in patients undergoing AVR with a small SJMHP . Carrel et al demonstrated that the hemodynamic performance of the 21 HP in vivo has been better than that of the 21 SD and that it corresponded closely to that of the 23 SD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations